2020
DOI: 10.18203/2319-2003.ijbcp20201765
|View full text |Cite
|
Sign up to set email alerts
|

A review of pharmacological effects of xylopic acid

Abstract: Xylopic acid (15β-acetyloxy-kaur-16-en-19-oic acid) is a kaurene diterpene that can be obtained from various Xylopia spp. Xylopic acid has demonstrated several pharmacological activities in vitro and in vivo. The compound has shown promising effect as a potent analgesic, anti-inflammatory and anti-allergic agent. Xylopic acid is a CNS depressant and was able to ameliorate anxiety-like symptoms in mice in addition to its neuroprotective effects. Deleterious effects of xylopic acid on the reproductive system of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…An example of one of such herbs is the Xylopia aethiopica. Studies have shown that the plant has anti-inflammatory, antimicrobial, analgesic, antiparasitic, and antioxidant properties [3][4][5]. In Ghana, the fruit is used by traditionalists to manage a wide range of disorders as it is believed to have curative effects on dyspepsia, cough, pain, and parasitic infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of one of such herbs is the Xylopia aethiopica. Studies have shown that the plant has anti-inflammatory, antimicrobial, analgesic, antiparasitic, and antioxidant properties [3][4][5]. In Ghana, the fruit is used by traditionalists to manage a wide range of disorders as it is believed to have curative effects on dyspepsia, cough, pain, and parasitic infections.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, the fruit is used by traditionalists to manage a wide range of disorders as it is believed to have curative effects on dyspepsia, cough, pain, and parasitic infections. It is equally used as a spice in the preparation of dishes such as porridge (Hausa Koko), sobolo, other African cuisines, and soups [5,6]. Some food industries use it as a flavoring agent, and in some cosmetic industries, it is used as an agent for fragrance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Xylopic acid, a kaurene diterpene from Xylopia aethiopica (Annonaceae), possesses many therapeutic benefits. Among these is its antinociceptive effect [10][11] . Woode et al previously reported xylopic acid's antinociceptive mechanism 11 .…”
Section: Introductionmentioning
confidence: 99%